ANALISA CAPAIAN PELAKSANAAN PEKERJAAN LAYAK DAN PERTUMBUHAN EKONOMI DALAM SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI KABUPATEN BOGOR - Aminda, Renea Shinta; Aminda, Annisa; Rizki, Muhamad (JPMUJ, 2024)
Sustainable Development Goals (SDGS) is currently a big concept. There is an increase in the number of unemployed and a decrease. The aim of this research is to analyze the achievements of implementing decent work and economic growth in the Sustainable Development Goals (SDGS) in Bogor Regency. The population in this research is SKPD Bogor Regency, and the sample used a Purposive Sampling technique and the analysis method used was the descriptive method and the projection method, especially exponential. The results obtained after the data analysis process were that there were several indicators that were projected to not reach their targets in 2022 and 2023, namely the GDP growth rate per capita. (ADHK), the proportion of informal employment in the non-agricultural sector, based on gender, and the open unemployment rate based on age group, these targets will be achieved on average in 2024, including the GDP growth rate per capita. (ADHK) and the open unemployment rate based on type of age group will be achieved in 2026 or the next 5 years, these 2 indicators are the main role that can be assessed over a longer period of time in achieving them.